Oxidant stimulation for enhancing coal seam permeability: Swelling and solubilisation behaviour of unconfined coal particles in oxidants. (1st June 2018) - Jing, Zhenhua; Balucan, Reydick D.; Underschultz, Jim R.; Steel, Karen M.
Highlights: Oxidant solutions reacted with coal particles to cause swelling/breakage rather than etching. Degree of swelling is significant in NaClO (up to 15%) and KMnO4, but only slight in K2 S2 O8 . Extent of dissolution is also significant in NaClO and KMnO4 (max. 15%). Swelling/breakage and dissolution suggest physical and chemical mechanisms occurring. Swelling may decrease coal permeability while breakage/dissolution may provide enhancements. Abstract: Low permeability renders a significant fraction of coal seam gas (CSG) resources sub-economic. An effective permeability enhancement strategy is thereby crucial in monetising a large proportion of low permeability CSG resources. This paper introduces the concept of using oxidants for permeability enhancement, describes a practical screening method to evaluate potential oxidants and provides knowledge about the coal behaviour in oxidants. A test based on time-lapse photography and image analysis of coal particles immersed in liquid oxidants was used to assess the extent and rate of change of coal particle size. Complementary leaching tests determined the extent of coal solubilisation by quantifying the change in coal mass and leachate organic content. The swelling profiles of coal particles hand-picked from a low permeability CSG coal core (Bowen Basin, Australia) were first examined in solutions of potassium chloride, and then pyridine for the purpose of method development and validation. Finally, the swelling ratio, SR, and rate of swelling Sr (% area change per 6 h), of coal particles immersed in oxidising solutions of sodium hypochlorite (0.1%, 1% and 10% NaClO), potassium permanganate (0.015%, 0.03%, 0.1%, 1%, 3% and 5% KMnO4 ), hydrogen peroxide (1%, 3%, 10% and 30% H2 O2 ) and potassium persulfate (1% and 3% K2 S2 O8 ) were examined. Results provide evidence for coal solubilisation (maximum mass loss = 15%) and the propensity to swell (maximum particle size increase = 15%) in all the candidate oxidant stimulants as well as coal breakage in specific oxidants and at specific concentrations (1% NaClO and 3%, 5% KMnO4 ). The swelling and solubilisation of the coals used in this study tends to increase with higher oxidant concentrations. Anisotropic swelling was also clearly observed in 1% NaClO. Coal reacted vigorously with NaClO and KMnO4, but only slightly with K2 S2 O8 and H2 O2 . Massive coal solubilisation occurs in NaClO and KMnO4, but negligible in K2 S2 O8 and H2 O2 . In terms of coal oxidation to enhance permeability, NaClO and KMnO4 seem to be more promising than K2 S2 O8 and H2 O2 . For the situation of in situ application, it remains unclear if the net effect of coal swelling and coal solubilisation will increase or decrease permeability. In addition, coal breakage may lead to void space or new cracks in the coal matrix, which could have the potential to increase the coal permeability. Confined core-flooding tests that simulate in situ conditions are required to elucidate this behaviour.